Assessment of Abdominal Constrictor’s Forces for Informing Computational Models of Orthostatic Hypotension - Syed, Faiz; Jose, Rejath; Devine, Timothy; Coletti, Chris; Toma, Milan (Materials, 2022)
Orthostatic hypotension is defined as a sudden drop in blood pressure upon standing from a sitting or supine position. The prevalence of this condition increases exponentially with age. Nonpharmacological treatments are always the first step in the management of this condition, such as the use of an abdominal constriction belt to optimize the blood volume in the abdomen. A multitude of clinical trials have shown the efficacy of elastic abdominal compression as well as compression using an inflatable bladder; however, there are currently few accessible consumer products that can provide abdominal compression by using an inflatable bladder that ensures the correct amount of pressure is being exerted on the subject. This study serves to quantitatively analyze forces exerted in inflatable abdominal binders, a novel treatment that fits the criterion for a first-line intervention for orthostatic hypotension. Quantitative values aim to indicate both the anatomic regions of the body subjected to the highest pressure by abdominal binding. Quantitative values will also create a model that can correlate the amount of compression on the subject with varying levels of pressure in the inflatable bladder. Inflatable binders of varying levels of inflation are used and localized pressure values are recorded at 5 different vertical points along the abdomen in the midsternal line and midclavicular line, at the locations of the splanchnic veins. These findings indicate both the differences in the compressive force applied through elastic and inflatable binding, as well the regions on the abdomen subject to the highest force load during compression by an abdominal binder. A medical manikin called the iStan Manikin was used to collect data. The pressure values on a manikin were sensed by the JUZO pressure monitor, a special device created for the purpose of measuring the force under compressive garments. The pressure inside the inflatable bladder was extrapolated from a pressure gauge and the pressure was recorded at different degrees of inflation of the belt (mmHG) along two different areas of the abdomen, the midsternal line and the midclavicular line, to discern differences in force exerted on the patient (mmHG). Computational studies on the data from the JUZO pressure monitor as well as the data from the pressure gauge on the inflatable bladder allow us to create a model that can correlate the amount of pressure in the inflatable bladder to the amount of pressure exerted on the belt, thus making sure that the patient is not being harmed by the compressive force. The results of our study indicate that there is no significant difference between the pressures exerted on the midsternal and midclavicular lines of the body by the abdominal binder and that no significant difference exists between the external pressure measured by the inflatable belt and the pressure sensed on the human body by the JUZO sensor; however, we were able to extrapolate an equation that can tell the user the amount of pressure that is actually being exerted on them based on the pressure in the inflatable bladder as recorded by the gauge.